Pengaruh Kompetensi Guru terhadap Hasil Belajar Siswa Kelas XI di SMA Negeri I Adonara Barat Tahun Ajaran 2022/2023 - Maria Anita Titu; Reinaldis Masi; Sirilus Karolus Keroponama Keban (STKIP PGRI SITUBONDO, 2023)
Abstract: This study aims to determine the effect of teacher competence on student learning outcomes in class XI SMA Negeri 1 Adonara Barat. The population and sample in this study amounted to 50 students. The data collection method in this study was a questionnaire or questionnaire. The data analysis technique used was simple linear regression analysis. Based on the results of data processing, the results obtained are tcount = 5,353 and ttable = 1.677 with Fcount = 28,660 greater than Ftable = 2.565 with a significance level of 0.000, less than α = 0.05. the conclusion that teacher competence has a significant influence on learning outcomes. This can be proven by the problems that exist in the research being answered. The hypothesis states that there is a significant influence between teacher competence on learning outcomes at SMA Negeri 1 Adonara Barat for the 2022/2023 academic year is accepted. And the determinant coefficient (Rsquare is 37.4% which means that the teacher's competence gives a proportion of 37.4% to learning outcomes. Keywords: Teacher Competence. Learning outcomes